Developing competency to manage diversity : readings, cases & activities - Cox, Taylor, Jr., 1949- (Berrett-Koehler Publishers ; Publishers Group West [distributor], 1997)
Develop a critical competency for today's organizations - the ability to successfully manage diversity. Builds on the author's acclaimed volume, Cultural Diversity in Organizations; organizes learning and skill-building for diversity around thirty-one activities that can change behavior; addresses a wide range of diversity issues through twenty-three timely readings; integrates ideas from the academic world with real-life experience in six detailed case studies; and provides managers with tools they need to successfully managed a diverse workforce.
Keywords: Diversity in the workplace.; Cultural pluralism.; Cultural Diversity; Multiculturalisme en milieu de travail.; Diversité culturelle.; BUSINESS & ECONOMICS -- Workplace Culture.; BUSINESS & ECONOMICS -- Human Resources & Personnel Management.; Diversity in the workplace; Organisatiecultuur.; Personeelsmanagement.; Gelijke behandeling.